LATIHAN LARI 100 METER INTENSITAS MAKSIMUM MENINGKATKAN ASAM LAKTAT DARAH - I Made Yoga Parwata (Sport and Fitness Journal, 2018)
Exercise is an activity that is open to everyone according to pleasure, ability and opportunity. Exercise is a form of part of the effort to build an objective, competitive, and sportsmanship. Success in the field of sports development can be measured by achievement of achievement level. Achievement of copper is the result of the process of coaching and training that has been implemented systematically. This study aims to determine whether there was a relationship between anaerobic activity maximum run 100 meters to increase lactic acid blood level. This research was done by descriptive method correlation. The sample in this study as many as 24 people who meet the criteria of inclusion and exclusion, selected randomly simple. This research was conducted at Ngurah Rai Stadium Denpasar on December 21, 2015. The data was collected on the morning of 07.30-09, 30 Wita. The correlation test results showed a strong relationship with rxy = 0.793 and p = 0,000 indicated that there was a significant relationship between the speed of 100 meter run and the increase of lactic acid level with p value < 0,05. There was a strong and significant relationship between the maximum anaerobic activity of running 100 meter to the blood lactic acid level in FPOK student of IKIP PGRI Bali.